Influence of Peanut Extract on Bleeding Time - Frampton, V. L; Lee, Louise S.; Morris, Nelle J.; Boudreaux, H. B (Thrombosis and Haemostasis, 1966)
The bleeding time of transected arterioles in the cheek pouch of hamsters ingesting an alcohol extract of defatted peanuts was shortened to about 3/4 that of untreated control animals. Solvent separation and chromatographic methods were used in producing a concentrate representing 0.0025% of the original peanut kernels. The concentrate shortened bleeding time, caused vasoconstriction of transected arterioles after hemostasis and induced strong contraction of isolated duodenum preparations. The contraction response of duodenum was used as a guide for separation methods. The activity on duodenum was high at concentrations of 10-7 g/ml of Tyrode’s solution. Preliminary determinations indicate that the active factor might be a lactone but impurities in the best concentrates preclude its positive identification. It is soluble in water, sparingly soluble in ethanol and methanol, very slightly soluble in boiling acetone, insoluble in butanol, chloroform, diethyl ether, 2,2-dimethoxypropane, pyridine and petroleum ether. A possible role in hemostasis is discussed.